Identification of neurohypophysial hormones and the role of VT in the parturition of pregnant seahorses (Hippocampus erectus) - Zhang, Huixian; Liu, Yali; Qin, Geng; Lin, Qiang (Frontiers in Endocrinology, 2022)
Neurohypophysial hormones regulate the reproductive behavior of teleosts; however, their role in the gestation and parturition of ovoviviparous fishes with male pregnancy (syngnathids) remains to be demonstrated. In the present study, the cDNA sequences of arginine vasotocin (VT) and isotocin (IT) from the lined seahorse (Hippocampus erectus) were cloned and identified. We observed that the mature core peptides of seahorse VT and IT were conserved among teleosts. In the phylogenic tree, seahorse VT and IT clustered independently with teleost VT and IT. The tissue distribution patterns of VT and IT were similar, and both were highly expressed in the brain, gills, and gonads. Interestingly, they were also expressed to some extent in the brood pouch. In situ hybridization revealed that VT and IT mRNA signals in the brain were mainly located in the preoptic area region of the hypothalamus. Intraperitoneal administration of the VT core peptide to pregnant seahorses induced premature parturition, stimulated gonadotropins release, increased serum estrogen levels, and decreased prolactin secretion. Moreover, VT injection up-regulated the mRNA expression of the membrane estrogen receptor in the brood pouch. In summary, neurohypophysial hormones promote premature parturition by regulating estrogen synthesis through the hypothalamus-pituitary-gonad axis.